1985
DOI: 10.1148/radiology.155.1.3975392
|View full text |Cite
|
Sign up to set email alerts
|

The cervical neural foramina: correlation of microtomy and CT anatomy.

Abstract: The CT appearance of the cervical neural foramina and contents is described in detail. Nineteen cervical spine specimens were studied with CT and corresponding cryomicrotomy in direct axial, sagittal, coronal, and oblique planes. Both ventral and dorsal nerve roots can be identified in the foramen's lower portion at or below the disk level. The dorsal nerve roots and ganglion contact the superior facet. The ventral nerve roots contact the uncinate process and bottom of the neural foramen. The ventral nerve roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
4

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 0 publications
0
27
0
4
Order By: Relevance
“…The dimensions of the cervical foramen are of clinical importance in the diagnosis of foraminal herniated disc and stenosis. Anatomic studies have described the cervical neural foramen as a 4-5 mm long bony canal through which the cervical nerve root passes anterolaterally at approximately a 45°angle with respect to the coronal plane and downward 10-15°with respect to the axial plane [2,10]. The ventral and dorsal nerve roots are located in the inferior portion of the neural foramen at or below the disc level.…”
Section: Discussionmentioning
confidence: 99%
“…The dimensions of the cervical foramen are of clinical importance in the diagnosis of foraminal herniated disc and stenosis. Anatomic studies have described the cervical neural foramen as a 4-5 mm long bony canal through which the cervical nerve root passes anterolaterally at approximately a 45°angle with respect to the coronal plane and downward 10-15°with respect to the axial plane [2,10]. The ventral and dorsal nerve roots are located in the inferior portion of the neural foramen at or below the disc level.…”
Section: Discussionmentioning
confidence: 99%
“…4,9,11,14 The vertical diameter of the foramen has been reported to be approximately twice that of the anteroposterior diameter, and the foramen encompasses the spinal nerves, fatty tissues, and small veins. 4,11,23,30 While the cervical anatomy and the relationship between the contents of the neural foramina have been documented through numerous published studies, 3,8,9,10 our review of the literature found no normative data establishing the dimensions of the cervical intervertebral foramen in vivo, nor how these dimensions are altered with various changes in the position of the head or neck.…”
mentioning
confidence: 77%
“…Blood is drained by vessels that flows into the perimedullary veins. There are two pathways at these veins [38]. The epidural venous plexuses are in communication with the extravertebral system through the intervertebral foraminal veins, by two veins [6,10,12].…”
Section: The Veinsmentioning
confidence: 99%
“…The posterior (sensory) root, is three times larger than the anterior root, and is composed of four to ten rootlets that penetrate the posterior collateral sulcus. It is located posteriorly and superiorly to the anterior root [38]. The cervical nerve roots extend anterolaterally at a 45° angle to the coronal plane and inferiorly at about 10° to the axial plane [9].…”
Section: The Nerve Rootsmentioning
confidence: 99%
See 1 more Smart Citation